Engaging in Community Issues and Contributing to Reforming It in Prison Literature The Poetry of Abi Al-Ala Al-Maari as a Model: ARABIC LITERATURE - Essarraoui Abdessadeq (Al-Ḍād Journal, 2022)
The organic intellectual, in the expression of Gramsci, carries a great concern towards the society to which he belongs. This is because he is committed to harnessing his culture and literature that he writes to raise the issues of his society and its problems. Therefore, this study comes to adopt a model for this educator, which gives an ideal image of a sense of responsibility for this person towards his community, and the need to engage in his issues and the problems that he answers in all cases in which this educated is, even in the case of imprisonment and negation, through the form of Abu Al -Ala Al -Maari poetry. This was a milestone among the writers and poets of his time. He was an active model from within the society to which he belongs, even though he remained trapped in the darkness of the blindness that afflicted him from a young age, and remained a prisoner from inside the cage of the walls of his house in which he lived until his last age. Despite all this, he contributed to the criticism of the customs and pests that inhabited his society, and became involved in advocating its reform and reform Based on an investigative approach, this study examines the motives for Al-Maarri’s imprisonment and the most important social issues that he raised in his poetry from his own prison. Keywords: prison literature- Al-Maari- Reform of the Society.